Accuracy of Xpert MTB/RIF Ultra for the diagnosis of tuberculosis in adult patients: a retrospective cohort study - Chintan Kaswala; Yvonne Schmiedel; Debasree Kundu; Mithun Mohan George; Divya Dayanand; Emily Devasagayam; Abi Manesh S; Selwyn Selva Kumar; Joy S Michael; Marilyn M Ninan; Geeta Chacko; Anand Zachariah; et al. (International Journal of Infectious Diseases, 2022)
Objectives: The value of the “trace” result in Xpert Ultra for diagnosing active tuberculosis (TB) remains unclear. Our study evaluated the diagnostic accuracy of Xpert MTB/RIF Ultra (Xpert Ultra) (Cepheid, Sunnyvale, USA) over Xpert MTB/RIF (Xpert) (Cepheid, Sunnyvale, USA) and mycobacterial culture when compared with a composite reference standard (CRS).Methods: A retrospective single-center observational study was conducted in a tertiary care hospital in South India. Over three months, patients (aged ≥15 years) data on Xpert Ultra tests and mycobacterial culture of pulmonary and extrapulmonary samples were extracted from their electronic medical records. Patients were defined as TB cases based on the CRS criteria. Sensitivity, specificity, positive and negative predictive values of diagnostic tests were calculated by comparing them to the CRS.Results: Xpert Ultra was more sensitive (87.8%) than Xpert (72.1%) and culture (44.1%). The specificity of Xpert Ultra was lower (98.1%) than those of Xpert (100%) and culture (100%). The sensitivity (92%) and specificity (100%) of Xpert Ultra were highest when performed on pus samples.Conclusions: Xpert Ultra with the trace category is superior to the conventional Xpert, and mycobacterial culture in identifying TB.